Educational social skills of parents of children with ASD: characterization and relationship with the social skills of children - Girotto Agostini, Júlia Maria (2023)
This study aimed to characterize the repertoire of educational social skills of parents of children with Autism Spectrum Disorder and to relate it to their children’s social skills. 62 parents /caregivers of children between 3 and 12 years old attended in Specialized Rehabilitation Services of a micro-region in Zona da Mata /Minas Gerais, Brazil participated. The Social Educational Skills Inventory (IHSE-Del Prette) and the Brazilian version of Social Skills Inventory, Behavior Problems and Academic Competence of Children (SSRS) were used. A positive correlation was obtained between the general scores of the two instruments and most factors. The parents’ ability to talk /dialogue proved to be strong predictors of children’s social skills. The implications of the results for interventions with parents of children with autism are discussed.